The global technology revolution 2020, in-depth analyses : bio-nano-materials-information trends, drivers, barriers, and social implications - Silberglitt, R. S. (Richard S.) (Technical report (Rand Corporation), 2006)
In 2020, areas of particular importance for technology trends will include biotechnology, nanotechnology, materials technology, and information technology. The authors of this report assessed a sample of 29 countries across the spectrum of scientific advancement (low to high) with respect to their ability to acquire and implement 16 key technology applications (e.g., cheap solar energy, rural wireless communications, genetically modified crops). The study's major conclusions are that scientifically advanced countries such as the United States, Germany, and Japan will be able to implement all key technology applications evaluated; countries that are not so scientifically advanced will have to develop significant capacity and motivation before barriers to technology implementation can be overcome; and public policy issues in certain areas will engender public debate and strongly influence technology implementation.